Розвідки у Гадяцькому р-ні Полтавської обл. у 2009 р. - Шерстюк, В.В.; Мироненко, К.М. (Археологічні дослідження в Україні, 2010)
In 2009, officials of the Poltava Centre of Archaeology conducted an eventual archaeological prospecting in Hadyach Region of Poltava Oblast, mainly in suburbs of Knyshivka village. Already known Brovarky burial ground of the Scythian period was researched, a new ground necropolis of a settlement of the same period in Duchyntsi village was discovered, and a hill-fort of Romny culture and Ancient Rus period in Knyshivka village was examined.